Evaluasi Ruang Terbuka Hijau di Kecamatan Sleman Kabupaten Sleman - Vinda Catur Nugroho (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2015)
The development of urban area gives negative impact on the environmental aspects, such as the decreasing of areas for green open space. Therefore, it is necessary to implement the research about evaluation of green open space. This research aims to evaluate availability, form and create green open space structuring model in the district of Sleman. The research was conducted by survey method which technical implementation was done by observation, questionnaires, and primary and secondary data collection. The choice of location observations made purposively. The data that has been collected was analyzed descriptively. The results of this research showed that the district of Sleman have public green open space which is less that 35.84 hectares or 1.14% of the area that 624.4 hectares, was referred to UU RI No. 26 year 2007. A green open space structuring model as a reference model to increased the value of aesthetic, functional and to increast the existing green open spaces in the district of Sleman can be done with the developing of city parks, city forests, roadside plants and water fountains that have a functional and aesthetic value.